Cellular Mechanisms Underlying B Cell Abnormalities in Patients With Gain-of-Function Mutations in the PIK3CD Gene - Wang, Wenjie; Min, Qing; Lai, Nannan; Csomos, Krisztian; Wang, Ying; Liu, Luyao; Meng, Xin; Sun, Jinqiao; Hou, Jia; Ying, Wenjing; Zhou, Qinhua; Sun, Bijun; et al. (Frontiers in Immunology, 2022)
Background Activated phosphoinositide 3 kinase (PI3K) -delta syndrome (APDS) is an inborn error of immunity with variable clinical phenotype of immunodeficiency and immune dysregulation and caused by gain-of-function mutations in PIK3CD. The hallmark of immune phenotype is increased proportions of transitional B cells and plasmablasts (PB), progressive B cell loss, and elevated levels of serum IgM. Objective To explore unique B cell subsets and the pathomechanisms driving B cell dysregulation beyond the transitional B cell stage in APDS. Methods Clinical and immunological data was collected from 24 patients with APDS. In five cases, we performed an in-depth analysis of B cell phenotypes and cultured purified naïve B cells to evaluate their survival, activation, Ig gene class switch recombination (CSR), PB differentiation and antibody secretion. We also analyzed PB differentiation capacity of sorted CD27-IgD- double-negative B (DNB) cells. Results The patients had increased B cell sizes and higher proportions of IgM+ DNB cells than healthy controls (HC). Their naïve B cells exhibited increased death, impaired CSR but relatively normal PB differentiation. Upon stimulation, patient’s DNB cells secreted a similar level of IgG but a higher level of IgM than DNB cells from HC. Targeted therapy of PI3K inhibition partially restored B cell phenotypes. Conclusions The present study suggests additional mechanistic insight into B cell pathology of APDS: (1) decreased peripheral B cell numbers may be due to the increased death of naïve B cells; (2) larger B cell sizes and expanded DNB population suggest enhanced activation and differentiation of naïve B cells into DNB cells; (3) the impaired CSR yet normal PB differentiation can predominantly generate IgM-secreting cells, resulting in elevated IgM levels.